Особливості морфоструктури насіння актинідії гібридного походження - Skripchenko, N.V.; Sytnjanskaya, N.P.; Moroz, P.А. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2008)
The results of morphostructure investigation of the seeds of sort Kyivska krupnoplidna actinidia, which was obtain in result of interspecies hybridization, and the seeds of Actinidia purpurea Rehd. and A. arguta (Siebold et Zucc.) Planch. ex Miq., which were used for selection of this sort, are presented. It was established, that the seeds of hybrid actinidia carry on yourself the morphostructure features of initial actinidia species and some new ones, which may be considered as the display of plant adaptation for new growing conditions.